Measurements of groundwater, hydrodynamics, and sand characteristics at a dissipative sea turtle nesting beach - Jakob C. Christiaanse; José A. A. Antolínez; Meye J. van der Grinten; Falco Taal; Jens Figlus; Timothy M. Dellapenna; Benjamin Ritt; Christopher D. Marshall; Peter A. Tereszkiewicz; Nicholas Cohn; Edward J. Majzlik; Ad J. H. M. Reniers (Scientific Data)
Abstract Beach groundwater and nearshore hydrodynamic data were collected during a field experiment along two dissipative beach transects on Galveston Island, Texas, in the fall of 2023. The monitored beaches serve as nesting habitat for the critically endangered Kemp’s ridley sea turtle. Conditions ranged from calm to stormy, with two storms occurring during the experiment, inundating the entire beach up to the dune toe. Collected hydrodynamic data include readings from pressure loggers submerged in the foreshore and mounted in groundwater wells in the backshore, data from two wave buoys about 1.5 km offshore, and GoPro timestacks of the instantaneous waterline (wave runup). Other collected data include bathymetry and topography surveys, subsurface temperature and moisture content readings, and sediment characteristics. This comprehensive dataset can be used to (1) study relevant beach inundation and groundwater processes, including their effect on the local ecosystem (e.g., repeated flooding of sea turtle nests), (2) study the propagation of nearshore hydrodynamic processes into the beach matrix and groundwater table, and (3) validate existing beach groundwater models.